Simulasi Rancang Bangun Alat Pemberi Pakan Ayam Dan Monitoring Suhu Kandang - kusumo, bayu (Universitas Pancasakti, 2024)
In the livestock sector in Indonesia, the manual method is used, namely the breeder must put the feed into the feed container. Breeders also have to check the temperature in the cage and this certainly requires a lot of effort and time for livestock management. The application of IoT in chicken farms can be implemented to help farmers monitor and provide automatic feed. Of course this will help livestock farming activities using automatic feeders and temperature controllers that can be monitored anywhere with just a smartphone. The automatic system consists of an automatic system that provides ideal air and a chicken feed system. Determination of tool specifications and manufacture that aims to find the form. Testing the sending of data on the Telegram application has been carried out 10 times. Sending data has a success percentage of 100% and an average delay of 17.40 seconds. Testing of sending data for the feeding time test on an automatic feed system was carried out 2 times. This test aims to open the valve in the dining area during breakfast and evening meals. The automatic feed system feature can be adjusted according to the needs of animal feed, with the intention that the amount of feed per day can be adjusted easily. Sending mealtime test data has a success percentage of 100%..